Direct Simulation of Ternary Mixture Separation in a ZIF‐8 Membrane at Molecular Scale. Issue 11 (16th August 2019) - Namsani, Sadanandam; Ozcan, Aydin; Yazaydın, A. Özgür
Abstract: Separation of H2 in a ZIF‐8 membrane from a syngas mixture composed of CO2, H2, and N2 at 300 K and 35 atm is simulated with the concentration gradient driven molecular dynamics (CGD‐MD) method. Steady‐state fluxes are computed to predict the H2 selectivity of the ZIF‐8 membrane using four different flexible force fields developed for ZIF‐8. The permselectivities predicted by the CGD‐MD method are compared with those obtained from the grand canonical Monte Carlo+equilibrium molecular dynamics (GCMC+EMD) approach, which is based on the solution‐diffusion model and widely used to predict permselectivities for mixture separations. The permselectivities obtained by using the CGD‐MD method accurately predict that ZIF‐8 is H2 selective over CO2 and N2 . On the other hand, permselectivities predicted with the GCMC+EMD approach are found to be incorrect, that is, ZIF‐8 not selective for H2 . The study suggests that a reliable non‐equilibrium molecular dynamics approach should be employed in order to obtain accurate predictions for the permselectivity of a membrane for a multicomponent mixture separation process which happens at moderate or high pressure conditions. Abstract : Non‐equilibrium molecular dynamics simulations of membrane separation of a ternary mixture at high pressure is carried out by using the concentration gradient driven molecular dynamics (CGD‐MD) method. While the permselectivities obtained with the CGD‐MD method are found to be accurate, permselectivities obtained by using the grand canonical Monte Carlo+equilibrium molecular dynamics approach are found to be incorrect.